Future perspectives of sustainable development: An innovative planning approach to inner areas. Experience of an Italian alpine region. (December 2019) - Battaglia, Massimo; Annesi, Nora; Pierantoni, Ilenia; Sargolini, Massimo
Highlights: The support of an actor who has a detailed view of the context represents a strategic collaboration that can ensure the success of a plan. Collaborative model (Sagor, 2000 ) can guide the design of those place-based polices that can better ensure a sustainable long term development. The developed model demonstrates that it is possible to put in place a multilayer planning supported by the expertise of local actors. Collaboration of stakeholders is a good practice for the design and implementation of those activities which involve the integration of sectors. Abstract: " Futures " studies have treated the issue of place-based approach and bioregionalism planning as tool to achieve a sustainable development in areas characterized by exclusive natural peculiarities (Gray, 2007 ; Tonn, English, Turner, & Hemrick, 2006 ). After reviewing theories and cases concerning the re-launch of this kind of territories, the study introduces the concept of inner areas (Barca, 2009 ). Inner areas, described as a specific territorial weak category, are central to the European and Italian debate about territorial inequality and fragmentation. However, no methods to implement processes to develop inner areas have been officially identified. With these premises, this study presents a profile of a new territorial planning model of local development based on the implementation of multi-disciplinary and multi-stakeholder processes. New perspectives on sustainable long-term development, as well as the involvement of local stakeholders in planning choices, are central to this work. The focus of the study is an Italian inner area. In this study, the collaborative action-research model proposed by Sagor (2000) is transposed from the educational context into the field of sustainable regional planning for the first time. The aim is to suggest a sustainable local development pathway, by considering together local economic, naturalistic and cultural resources. The research demonstrates that a place-based approach for developing inner areas is achievable thanks to a multidisplinary and multistakeholder approach to territorial planning, aimed at reducing marginality (Pateman, 2011 ) and stimulating local economy (Sharma, 2000 ). The lessons learnt by the planning experience are analysed and the possible application of the Sagor model in future planning experiences is discussed.